A note on Euclidean spaces $\mathbb{R}^n$ and $n$-normed spaces - Idris, Mochammad (Hilbert Journal of Mathematical Analysis, 2023)
This article gives us a relation between Euclidean space $\mathbb{R}^n$ and a subspace of $X$ (an $n$-normed space) using properties of determinant of square matrices. Some functionals will be investigated on these spaces. Furthermore, we obtain definition of inner product and $m$-inner product with $m<n$ on the subspace of $X$.